ECTOPIC PREGNANCY: RISK FACTORS, DIAGNOSIS AND FERTILITY RESTORATION - Лариса Егоровна Фетищева; Галина Александровна Ушакова (The Publishing House Medicine and Enlightenment, 2017)
Ectopic pregnancy is the most common pathology in gynecologic practice, leading to the reduction and loss of reproductive function. Diagnosis of ectopic pregnancy in cases of its occurrence interrupts and intra-abdominal bleeding does not provide significant difficulties. Of interest is the search for ectopic gestational sac located in rare forms of ectopic pregnancy. Although progress has been made in the diagnosis and treatment of ectopic pregnancy is not possible to achieve reduction of complications associated with it.